The Galveston Hurricane - Brennan, Kristine; Nang ChanYeema (New York City, New York USA Chelsea House Publisher, 2002)
An account of the tragic Galveston hurricane of 1900 that claimed over six thousand lives.
Keywords: Adult Nonfiction